Effect of Coal and Coke Ash on Blast Furnace Slag Properties: A Comparison Between Pulverized Coal, Charcoal, Fossil‐Based Coke, and Biocoke. Issue 3 (22nd May 2021) - Heikkilä, Anne; Iljana, Mikko; Heikkinen, Eetu-Pekka; Koskela, Aki; Fabritius, Timo
Abstract : Blast furnace (BF) is the most used equipment for production of iron in the world. It is charged mainly with metallurgical coke and ferrous materials. When descending inside the BF, iron‐bearing materials start reducing and melting with other burden materials. This melting leads to the formation of so‐called primary slags from which the final slag is formed as materials descend inside the furnace. Each charge material has a unique effect on the total composition of the BF slag. Herein, the parts of the slag, which originate from ash of metallurgical coke and pulverized coal, and changes in the final slag compositions and properties are focused on. The global trend is to decrease the use of fossil‐based carbon by replacing it with bio‐based coal. Ash from coke and pulverized coal eventually dissolve in the final slag, affecting its properties. The purpose herein is to evaluate how BF slag composition changes when fossil‐based coke is replaced with biocoke and pulverized coal is replaced with charcoal. Based on mass balance calculations, these replacements have both increasing and decreasing effects on solidus and liquidus temperatures, viscosity, and CaO/SiO2 and MgO/Al2 O3 ratios depending on the used replacement materials. Abstract : The focus herein is on the parts of slag formed from ash of metallurgical coke and pulverized coal. Changes in blast furnace slag compositions are calculated and evaluated when fossil‐based coke is replaced with biocoke and pulverized coal is replaced with charcoal. The effects on solidus and liquidus temperatures, viscosity, as well as CaO/SiO2 and MgO/ Al2 O3 ratios are discussed.